Minnesota Resuscitation Consortium's Advanced Perfusion and Reperfusion Cardiac Life Support Strategy for Out‐of‐Hospital Refractory Ventricular Fibrillation. Issue 6 (13th June 2016) - Yannopoulos, Demetris; Bartos, Jason A.; Martin, Cindy; Raveendran, Ganesh; Missov, Emil; Conterato, Marc; Frascone, R. J.; Trembley, Alexander; Sipprell, Kevin; John, Ranjit; George, Stephen; Carlson, Kathleen; et al.
Abstract : Background: In 2015, the Minnesota Resuscitation Consortium (MRC) implemented an advanced perfusion and reperfusion life support strategy designed to improve outcome for patients with out‐of‐hospital refractory ventricular fibrillation/ventricular tachycardia (VF/VT). We report the outcomes of the initial 3‐month period of operations. Methods and Results: Three emergency medical services systems serving the Minneapolis–St. Paul metro area participated in the protocol. Inclusion criteria included age 18 to 75 years, body habitus accommodating automated Lund University Cardiac Arrest System (LUCAS) cardiopulmonary resuscitation (CPR), and estimated transfer time from the scene to the cardiac catheterization laboratory of ≤30 minutes. Exclusion criteria included known terminal illness, Do Not Resuscitate/Do Not Intubate status, traumatic arrest, and significant bleeding. Refractory VF/VT arrest was defined as failure to achieve sustained return of spontaneous circulation after treatment with 3 direct current shocks and administration of 300 mg of intravenous/intraosseous amiodarone. Patients were transported to the University of Minnesota, where emergent advanced perfusion strategies (extracorporeal membrane oxygenation; ECMO), followed by coronary angiography and primary coronary intervention (PCI), were performed, when appropriate. Over the first 3 months of the protocol, 27 patients were transported with ongoing mechanical CPR. Of these, 18 patients met the inclusion and exclusion criteria. ECMO was placed in 83%. Seventy‐eight percent of patients had significant coronary artery disease with a high degree of complexity and 67% received PCI. Seventy‐eight percent of patients survived to hospital admission and 55% (10 of 18) survived to hospital discharge, with 50% (9 of 18) achieving good neurological function (cerebral performance categories 1 and 2). No significant ECMO‐related complications were encountered. Conclusions: The MRC refractory VF/VT protocol is feasible and led to a high functionally favorable survival rate with few complications.